Il magistero di Fulvio Papi all’Università di Pavia (Materiali di Estetica. Terza serie, 2024)
The article examines Fulvio Papi's distinguished tenure as a professor of Theoretical Philosophy at the University of Pavia. It highlights Papi's philosophy as a responsible interaction with reality and his dynamic pedagogical approach, which encouraged student autonomy and integrated various intellectual traditions, from Renaissance studies to Marxist analysis. The piece also reflects on Papi's efforts to foster a vibrant intellectual community that crossed disciplinary boundaries, contributing significantly to academic and cultural discourse.
Keywords: philosophical education; Fulvio Papi; Theoretical Philosophy